Monitoring pesticides degradation in apple fruits and potential effects of residues on human health - Pogăcean, Manuela Olga; Hlihor, Raluca Maria; Gavrilescu, Maria (Journal of Environmental Engineering and Landscape Management, 2014)
The behaviour of 12 pesticides used in the treatment of a variety of apples in areal conditions from a Romanian orchard is studied, considering recommended dosages, different stages of fruit development, environmental and atmospheric conditions. Five treatments were applied in recommended dosage considering the phenological growth phases, at 23 days intervals between treatments. Pesticides degraded quickly in apples during the first days, when 30–50% from the initial concentration is lost. Pesticides residues at harvesting were below the Maximum Residue Level (MRL) in European Union, excepting tebuconazole and chlorothalonil. The estimated lifetime exposure dose was calculated based on pesticide concentrations in apples at harvesting, and average fruit consumption of 197.08 g/ person/day in EU-27 during 2011. These doses for adults and children were below the reference dose (RfD) for each pesticide, suggesting a negligible risks for consumers. Hazard indices below 1 demonstrate that the studied pesticides do not generate health risks to humans.First published online: 18 Mar 2014